2015
DOI: 10.1259/bjr.20150353
|View full text |Cite
|
Sign up to set email alerts
|

Digital breast tomosynthesis at screening assessment: are two views always necessary?

Abstract: Objective: The current recommendation from the UK National Health Service Breast Screening Programme is that digital breast tomosynthesis (DBT) can be used for further assessment of possible screen-detected softtissue abnormalities in place of spot compression views and when used should be performed in two projections. The aim of the study was to assess whether twoview DBT is necessary if the abnormality is seen only in one view on initial full-field digital mammography (FFDM). Methods: 617 cases with possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The evidence to date is inconclusive on this point. Haq and colleagues investigated the question with Hologic DBT and found that in 31 malignant soft-tissue lesions seen on only one view at primary screening, DBT demonstrated the lesion on the same or on both views at assessment and never on the opposite view alone, indicating that a single DBT view in the screening projection more clearly demonstrating the lesion which prompted recall might be sufficient 29 . However, the study was not large enough to be conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence to date is inconclusive on this point. Haq and colleagues investigated the question with Hologic DBT and found that in 31 malignant soft-tissue lesions seen on only one view at primary screening, DBT demonstrated the lesion on the same or on both views at assessment and never on the opposite view alone, indicating that a single DBT view in the screening projection more clearly demonstrating the lesion which prompted recall might be sufficient 29 . However, the study was not large enough to be conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence that cancers may be seen on only one view, recent studies have explored the use of imaging with one-view-only MLO DBT (27)(28)(29). Lång et al (27) reported that the cancer detection rate at one-view MLO DBT was significantly better than at two-view DM (8.9 per 1000 vs 6.3 per 1000) and suggested that oneview MLO DBT could be a feasible stand-alone screening modality without DM.…”
Section: Teaching Pointsmentioning
confidence: 99%
“…Gennaro et al (28) found that one-view MLO DBT in combination with CC DM was superior to two-view DM for both lesion detection and characterization (overall and for benign lesions) and was noninferior to two-view DM for cancer detection and characterization of malignant lesions. Haq et al (29) argued against the use of second-view DBT in their study because of concerns regarding radiation dose. However, their study evaluated DBT as an alternative to spot-compression views because their patients all had an abnormality seen on one view at DM, with two-view DBT only used to determine if the abnormality seen at DM was seen at same-view DBT, orthogonalview DBT, neither, or both.…”
Section: Teaching Pointsmentioning
confidence: 99%
“…In most cases DBT is acquired in the same two planes as MG (CC and MLO). Newer studies point out that two DBT planes are not always necessary if MG has been performed in two planes [9]. Still DBT helps to improve diagnostic accuracy of detection of breast lesions compared to mammography alone [10,11].…”
Section: Introductionmentioning
confidence: 99%